ScFv Antibody: Principles and Clinical Application. (15th March 2012) - Ahmad, Zuhaida Asra; Yeap, Swee Keong; Ali, Abdul Manaf; Ho, Wan Yong; Alitheen, Noorjahan Banu Mohamed; Hamid, Muhajir
Abstract : To date, generation of single-chain fragment variable (scFv) has become an established technique used to produce a completely functional antigen-binding fragment in bacterial systems. The advances in antibody engineering have now facilitated a more efficient and generally applicable method to produce Fv fragments. Basically, scFv antibodies produced from phage display can be genetically fused to the marker proteins, such as fluorescent proteins or alkaline phosphatase. These bifunctional proteins having both antigen-binding capacity and marker activity can be obtained from transformed bacteria and used for one-step immunodetection of biological agents. Alternatively, antibody fragments could also be applied in the construction of immunotoxins, therapeutic gene delivery, and anticancer intrabodies for therapeutic purposes. This paper provides an overview of the current studies on the principle, generation, and application of scFv. The potential of scFv in breast cancer research is also discussed in this paper.